Do CEO characteristics impact corporate cash holdings? Insights from consumer goods companies listed on the Indonesia Stock Exchange - Muttaqin, Muhammad Sabil (Ifma Publishing, 2023)
This study aims to determine the effects of CEO characteristics on the corporate cash holdings of consumer goods industry firms listed on the Indonesia Stock Exchange from 2017–2021. The data used in this study were taken from annual reports of firms in consumer goods industry sectors published by the Indonesia Stock Exchange from 2017–2021. This study utilized a purposive sampling technique to obtain 210 observations. The research model used is an unbalanced panel data analysis with a fixed-effect model approach. The results show that gender diversity, CEO age and CEO education have positively associated with corporate cash holdings. However, CEO tenure has no a significant effect with corporate cash holdings